Context Analysis of User Decision based on social learning - Lee, B.Z.; Lu, H.Y.; Ma, S.H.; Song, X.P. (International Journal of Emerging Technologies in Learning (iJET), 2013)
We analyzed the context mechanism of usersâ?? decision behaviors in social tagging, and revealed the nature of social learning among users in social contexts. To improve the results of social tagging, we can select corresponding contexts according to usersâ?? given knowledge backgrounds and preferences. On the other hand, we can also recognize usersâ?? knowledge backgrounds and preferences according to their annotation results in relevant contexts.